Juridical Analysis of the Practice of Tender Conspiracy for Periodic Maintenance of the Bateballa-Jatia Cs Road in the Work Unit of the Public Works and Spatial Planning Office of Bantaeng Regency APBD 2017 Fiscal Year - Yogi Sumarsana Wibowo; Nanda Dwi Rizkia; Hardi Fardiansyah (PT FORMOSA CENDEKIA GLOBAL, 2023)
Various anti-competitive actions continue to occur in the procurement of government goods and services financed by the APBN and APBD. The intended anti-competitive practice is generally in the form of collusion in bidding for government procurement of goods and services. One of the cases of collusion is the KPPU decision No. 16/KPPU –I/2018 concerning violations of Article 22 of Law no. 5 of 1999 in the procedure for auctioning periodic maintenance work for the Batebella-Jatia CS road. The purpose of this research is to find out and analyze: (1) the occurrence of bid rigging in the procurement of goods and services; and (2) Application of the Tender Conspiracy Law against KPPU's Decision No. 16/KPPU-I/2018 concerning Tender for Periodic Maintenance Work for CS Batebella-Jatia Road. This research is a descriptive normative legal research using primary, secondary and tertiary legal sources. Data collection techniques using literature or documentation. Qualitative descriptive analysis was used in data analysis